Electrochemically converting micro-sized industrial Si/FeSi2 to nano Si/FeSi for the high-performance lithium-ion battery anode. (September 2021) - Ma, Qiang; Zhao, Yan; Hu, Zuojun; Qu, Jiakang; Zhao, Zhuqing; Xie, Hongwei; Xing, Pengfei; Wang, Dihua; Yin, Huayi
Abstract: Low-cost silicon (Si) feedstocks and a facile method to downsize the particle size are two determinants for the application of Si for the lithium-ion battery anode. Among various Si feedstocks, the industrial bulk ferrosilicon (b-Si/FeSi2 ) alloy is a promising Si resource, but decreasing the particle size and increasing the utilization of Si remain challenging. Herein, we report a self-driven alloying-electrochemical dealloying approach to converting the b-Si/FeSi2 to nano-sized Si/FeSi (n-Si/FeSi) in molten salts using Mg to extract one Si atom from one FeSi2 molecule by breaking down the FeSi–Si chemical bond and simultaneously forming Mg2 Si. Subsequently, the obtained FeSi and Mg2 Si are converted to nano Si and FeSi by electrochemically removing Mg from the Mg2 Si anode to the cathode, making a circular use of Mg and increasing the electroactive Si content. Moreover, the polydopamine-coated n-Si/FeSi (n-Si/FeSi@C) anode exhibits a high capacity of 1449.7 mAh g −1 after 500 cycles at 0.4 A g −1, and an extremely stable reversible capacity of 846.8 mAh g −1 is retained even after 1500 cycles at 2 A g −1 . Overall, this work provides an efficient method to convert industrial bulk Si/FeSi2 to nano-sized Si/FeSi by leveraging the chemical bonds of Fe–Si and Mg–Si. Graphical abstract: Image 1 Highlights: Low-cost industrial ferrosilicon is a promising feedstock for preparing anode materials for lithium-ion batteries. A self-driven alloying-electrochemical dealloying approach can convert micro-sized Si/FeSi2 to nano Si/FeSi. The conversion temperature is below the thermodynamic decomposition temperature. The n-Si/FeSi@C anode exhibits 846.8 mAh g −1 at 2 A g −1 after 1500 cycles.